HUBUNGAN ANTARA TINGKAT STRES DENGAN KEJADIAN NYERI KEPALA PRIMER PADA MAHASISWA S1 FISIOTERAPI FAKULTAS KEPERAWATAN UNIVERSITAS HASANUDDIN - Meilani, Meilani; Aras, Djohan; Hasyar, Andi Rizky Arbaim (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Mental disorders such as stress are problems that often occur in people of productive age. This can happen because at this time there is an increase in ability and the need to do various things that happen in the surrounding environment. Stress can have a negative impact on a person's health and well-being, for example related to neurological disorders that often occur, namely primary headaches. This study aims to determine the relationship between stress levels and the incidence of primary headaches in Physiotherapy undergraduate students at the Faculty of Nursing, Hasanuddin University. The sampling technique in this study was purposive sampling through a cross sectional approach. The number of samples in this study were 152 active undergraduate students of Physiotherapy, Faculty of Nursing, Hasanuddin University. Student stress levels were measured using the Depression Anxiety Stress Scale 42, while primary headaches used the Headache Intake Questionnaire, Cleveland Clinic Canada. In this study, the results showed that 36.8% of students did not experience stress and the other 63.2% experienced stress at different levels from mild to very severe. Furthermore, as much as 75,7% of the total respondents experienced primary headaches with the most frequent type of tension type headache. In this study the correlation test used was the Chi Square test and a p-value of 0.021 (p <0.05) was obtained, which means that there is a relationship between stress levels and the incidence of primary headaches in Physiotherapy undergraduate students at the Faculty of Nursing, Hasanuddin University. Keywords: Stress, Primary Headache, Student